A comparative study on dispersion of carbon nanotubes in (styrene‐butadiene rubber)‐based nanocomposites. Issue 1 (28th April 2015) - Salimi, A.; Naderi, G.; Khorshidi, V. Ghamgosar; Bakhshandeh, G. R.
Abstract : The efficient dispersion of carbon nanotubes (CNTs) is a challenging task in reaching the usable nanocomposites. In this study, a comparative analysis on dispersion of multiwalled CNTsmultiwalled carbon nanotubes (MWNTs) instyrene‐butadiene rubber (SBR) latex was carried out by using two anionic surfactants, sodium dodecyl benzene sulfonate and sodium lauryl sulfate. The MWNTs were first predispersed in distilled water using two surfactants individually followed by gentle mixing the MWNT predispersion into SBR latex. By using the technique of ultraviolet‐visible spectroscopy, the study on MWNT dispersion in aqueous media was focused on surfactant concentration, MWNT functionality, and ultrasonication time. The ultraviolet‐visible absorptions showed the positive effect of MWNT functionality in addition to surfactant concentration with no great effect of ultrasonication time over 15 min. In comparison with sodium lauryl sulfate, the existing benzene ring in the sodium dodecyl benzene sulfonate structure seems to result in higher adsorption of surfactant onto the MWNTs surface and, hence, better MWNT dispersion. The MWNT dispersion was further improved by using hydroxyl functionalized MWNTs mainly because of the formation of hydrogen bonding between the hydrophilic head of surfactant and the existing hydroxyl group of the functionalized MWNTs. After mixing the MWNT predispersion into SBR latex, the dispersion of MWNTs was further characterized by using electrical volume conductivity, microscopy technique, and rheological measurements. In rheometry tests of the lattices, the storage modulus at terminal zone was utilized for tracking the degree of MWNT dispersion in the nanocomposite. The pictures of scanning electron microscopy showed the efficiency of MWNT functionality in enhancing the degree of dispersion. In conductivity tests, the percolation threshold was obtained at about 1 part by weight per hundred parts of resin of the functionalized MWNT in dried film. J. VINYL ADDIT. TECHNOL., 23:28–34, 2017. © 2015 Society of Plastics Engineers